Visual noise effect on reading in three developmental disorders: ASD, ADHD, and DD. (June 2022) - Mihaylova, Milena Slavcheva; Bocheva, Nadejda Bogdanova; Stefanova, Miroslava Dimitrova; Genova, Bilyana Zaharieva; Totev, Tsvetalin Totev; Racheva, Kalina Ivanova; Shtereva, Katerina Atanasova; Staykova, Svetla Nikolaeva
Background and aims: Developmental disorders such as Autism Spectrum Disorder (ASD), Attention Deficit Hyperactivity Disorder (ADHD), and Developmental Dyslexia (DD) are reported to have more visual problems, oral language difficulties, and diminished reading skills in addition to their different diagnostic features. Moreover, these conditions also have increased internal noise and probably an impaired ability of external noise filtering. The aim of the present study was to compare the reading performance of these groups in the presence of external visual noise which disrupts the automatic reading processes through the degradation of letters. Methods: Sixty-four children and adolescents in four groups, ASD, ADHD, DD, and TD, participated in the study. Two types of stimuli were used – unrelated words and pseudowords. The noise was generated by exchanging a fixed number of pixels between the black symbols and the white background distorting the letters. The task of the participants was to read aloud the words or pseudowords. The reading time for a single letter string, word or pseudoword, was calculated, and the proportion of errors was assessed in order to describe the reading performance. Results: The results obtained showed that the reading of unrelated words and pseudowords differs in the separate groups of participants and is affected differently by the added visual noise. In the no-noise condition, the group with TD had the shortest time for reading words and short pseudowords, followed by the group with ASD, while their reading of long pseudowords was slightly slower than that of the ASD group. The noise increase evoked variations in the reading of groups with ASD and ADHD, which differed from the no-noise condition and the control group with TD. The lowest proportion of errors was observed in readers with TD. The reading performance of the DD group was the worst at all noise levels, with the most prolonged reading time and the highest proportion of errors. At the highest noise level, the participants from all groups read the words and pseudowords with similar reading speed and accuracy. Conclusions: In reading words and pseudowords, the ASD, ADHD, and DD groups show difficulties specific for each disorder revealed in a prolonged reading time and a higher proportion of errors. The dissimilarity in reading abilities of the groups with different development is most evident when the accuracy and reading speed are linked together. Implications: The use of noise that degrades the letter structure in the present study allowed us to separate the groups with ASD, ADHD, and DD and disclose specifics in the reading process of each disorder. Error type analysis may provide a basis to improve the educational strategies by appropriately structuring the learning process of children with TD, ASD, ADHD, and DD.